Relevansi Hadis tentang Larangan Membujang dengan Ilmu Kesehatan dan Sosial: Studi di Desa Bangun Jaya Kecamatan Tambusai Utara - Huda Hasibuan, Ramsil; Halim, Abdul (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to examine the social and psychological phenomena experienced by individuals who choose to remain single (tabattul) in Bangun Jaya Village, North Tambusai District, and how the community interprets the prohibition of singleness in the hadith of the Prophet Muhammad SAW in the context of everyday life. This study uses a qualitative approach with field study methods. Data were obtained through in-depth interviews, observation, and documentation with religious leaders, community leaders, and single individuals. The results show that long-term singleness without Islamic reasons has a negative impact on mental health, such as the emergence of depression, anxiety, loneliness, and behavioral disorders. In addition, the social stigma against single individuals also gives rise to psychological stress and social exclusion. In the context of the hadith, marriage is seen as a means of worship, self-protection, and the fulfillment of emotional needs in a halal manner. This study confirms that the recommendation for marriage in Islam not only has a spiritual dimension but is also closely correlated with an individual's psychological and social stability. Thus, marriage can be a form of preventive intervention against various risks of mental and social disorders arising from singleness.